2016
DOI: 10.1038/srep24724
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional, epigenetic and retroviral signatures identify regulatory regions involved in hematopoietic lineage commitment

Abstract: Genome-wide approaches allow investigating the molecular circuitry wiring the genetic and epigenetic programs of human somatic stem cells. Hematopoietic stem/progenitor cells (HSPC) give rise to the different blood cell types; however, the molecular basis of human hematopoietic lineage commitment is poorly characterized. Here, we define the transcriptional and epigenetic profile of human HSPC and early myeloid and erythroid progenitors by a combination of Cap Analysis of Gene Expression (CAGE), ChIP-seq and Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 68 publications
0
17
0
Order By: Relevance
“…ChIP experiments to detect H3K27Ac were performed as previously described (53). After 5 days of differentiation, −197 and AAVS1 HUDEP-2 bulk populations were collected for ChIP assays.…”
Section: Chip Assaymentioning
confidence: 99%
“…ChIP experiments to detect H3K27Ac were performed as previously described (53). After 5 days of differentiation, −197 and AAVS1 HUDEP-2 bulk populations were collected for ChIP assays.…”
Section: Chip Assaymentioning
confidence: 99%
“…The general patterns of retroviral integration are now well understood 1 . Gammaretroviral vectors integrate primarily within transcriptional regulatory elements (such as promoters and enhancers 100,101 ), whereas lentiviral vectors integrate primarily within active transcription units [102][103][104] . The integration pattern varies from one retroviral genus to another, indicating that the mere exposure of different sequences in open chromatin does not account for differences in targeting [102][103][104][105][106][107][108] .…”
Section: Optimizing Safetymentioning
confidence: 99%
“…Genome-wide integration and association studies showed that the MLV bias for TSSs is just a consequence of a more general preference of MLV PICs for active regulatory elements, particularly enhancers and super-enhancers. 17 , 18 , 76 , 77 , 78 High-resolution studies carried out in human HSPCs and committed progenitors, 17 , 18 , 78 T cells, 20 , 79 and keratinocytes 77 indicated that MLV ISs are highly clustered and occur almost exclusively in regions carrying epigenetic signatures of transcriptionally active regulatory regions, such as acetylation of H3K27 and H3K9, and mono-, di- and tri-methylation of H3K4 ( Figure 1 ). Symmetrically, typical heterochromatic marks, such as H3K27me3 and H3K9me3, are significantly under-represented at these genomic loci.…”
Section: Main Textmentioning
confidence: 99%